Orbital rhabdomyosarcoma in young adult: clinical case - Sumba, Andrea (2022)
Purpose: To report the diagnosis, treatment and evolution of an orbital alveolar rhabdomyosarcoma in a young adult patient. Clinical case. Male, 20 years old, consulted for retro-orbital pain, proptosis, headache, decreased vision, and fever. Once evaluated by ophthalmology, an infraorbital abscess was initially considered, a computed tomography scan was performed where an abscessed orbital tumor measuring 38x25mm was observed. Surgical drainage and biopsy were decided. The pathological anatomy reported solid variant of alveolar rhabdomyosarcoma. Orbital exenteration and then chemotherapy with a vincristine, dactinomycin, cyclophosphamide alternating with irinotecan was performed. He presented a rapid progression of the local and encephalic tumor for which he started radiotherapy with hemostatic palliative criteria, later dying from neurological complications. Conclusion. It is a rare disease in young adults and of complex management, which makes interdisciplinary work especially important to achieve a correct diagnosis and timely treatment, all of which conditions the prognosis of patients.